PERKEMBANGAN SISTEM PERATURAN PERUNDANG-UNDANGAN DI INDONESIA BERDASARKAN HUKUM TATA NEGARA - Stanley Kurniawan (Fakultas Hukum Universitas Tarumanagara, 2021)
Law is a system of regulations in which norms and sanctions are made with the aim of controlling human behavior to protect discipline, justice, and avoid the formation of chaos. Each country has certain legal rules that are different from other countries, including Indonesia. That means